Porządek publiczny a ochrona wizerunku jednostki w strefie publicznej - Wasiak, Dariusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
This article presents the problem of using the general clause of “public order” as an effective instrument to legitimize State’s actions leading to the violations of the good of persons – their image – in the public area. The interference is made through video monitoring system installed in the public area, which – being metaphorical panoptic theater – is also a space where one can lose the right to protection of his or her image. The author argues that a general clause embedded in art. 31(3) of the Constitution concerning the strength utilizing the instrumentality of the entire law system effectively denies the right of any individual to the prerogatives designed to protect actively their own image against such actions of the State.
Keywords: private life; public area; public order; image of individual; monitoring system